Evidence for climatic and oceanographic controls on terrigenous sediment supply to the Indian Ocean sector of the Southern Ocean over the past 63,000 years - Manoj, Madhusudhanan C.; Thamban, Meloth; Basavaiah, N.; Mohan, Rahul (Geo-Marine Letters, v.32/3, p. 251-265, 2011, doi:10.1007/s00367-011-0267-6, 2011)
Multiple proxy studies on sediment core SK 200/22a from the sub-Antarctic sector of the Indian Ocean revealed millennial-scale fluctuations in terrigenous input during the last 63,000 years. The marine isotope stages 1 (MIS 1) and MIS 3 are characterized by generally low concentrations of magnetic minerals, being dominated by fine-grained magnetite and titano-magnetite. Within the chronological constraints, periods of enhanced terrigenous input and calcite productivity over the last 63,000 years are nearly synchronous with the warming events recorded in Antarctic ice cores. An equatorward shift of the westerly wind system in association with a strengthening of the Antarctic Circumpolar Current (ACC) system may have promoted wind-induced shallow-water erosion around oceanic islands, leading to enhanced terrigenous input to the core site. Major ice-rafted debris events at 13–23, 25–30, 45–48 and 55–58 ka BP are asynchronous with δ18O and carbonate productivity records. This out-of-phase relation suggests that ice-sheet dynamics and ACC intensity were the primary factors influencing ice rafting and terrigenous input to the Indian sector of the Southern Ocean, with only limited support from sea-surface warming.